2020
DOI: 10.3389/fcell.2020.600926
|View full text |Cite|
|
Sign up to set email alerts
|

Zebrafish Models of Craniofacial Malformations: Interactions of Environmental Factors

Abstract: The zebrafish is an appealing model organism for investigating the genetic (G) and environmental (E) factors, as well as their interactions (GxE), which contribute to craniofacial malformations. Here, we review zebrafish studies on environmental factors involved in the etiology of craniofacial malformations in humans including maternal smoking, alcohol consumption, nutrition and drug use. As an example, we focus on the (cleft) palate, for which the zebrafish ethmoid plate is a good model. This review highlight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 149 publications
0
21
0
Order By: Relevance
“…Impaired formation of the ethmoid plate in zebrafish is considered to be homologous to cleft palate in mammals. 6,[37][38][39][40][41] However, ethmoid plate formation in zebrafish occurs by convergence of frontonasal and maxillary neural crest cells, which is analogous to the mammalian hard palate. 41 As a result, the soft palate that forms approximately one-third of the roof of the mammalian mouth 42 is absent in zebrafish.…”
Section: Discussionmentioning
confidence: 99%
“…Impaired formation of the ethmoid plate in zebrafish is considered to be homologous to cleft palate in mammals. 6,[37][38][39][40][41] However, ethmoid plate formation in zebrafish occurs by convergence of frontonasal and maxillary neural crest cells, which is analogous to the mammalian hard palate. 41 As a result, the soft palate that forms approximately one-third of the roof of the mammalian mouth 42 is absent in zebrafish.…”
Section: Discussionmentioning
confidence: 99%
“…While in vivo analysis of the behavior of key bone cells during bone remodeling in mice is invasive, by necessity depending on surgery and intravital imaging techniques [ 84 ], in fish osteoblasts and osteoclasts can be easily and non-invasively monitored in vivo using cell-specific reporter lines [ 85 ] ( Figure 3 A). Fish models are notable for understanding the craniofacial genetics [ 86 , 87 ], skeletal diseases, and even for the co-occurrence of craniofacial and limb disorders [ 88 ]. Contrary to mice studies, the development of the craniofacial skeleton, including the skull, can be observed in vivo and non-invasively, allowing researchers to investigate cellular behavior changes underpinning common craniofacial developmental conditions [ 89 ].…”
Section: Zebrafish As Animal Models To Accelerate Discoveries Of Huma...mentioning
confidence: 99%
“…However, studying G E in the human population is still challenging because of various reasons, including the difficulties in selecting genetic variants, the study design, the environmental factors of interest, and the temporality of environmental exposure ( Mcallister et al, 2017 ; Esposito et al, 2018 ). Animal models have been successfully used to analyze G E and its impact on developmental defects ( Eberhart and Parnell, 2016 ; Hong and Krauss, 2018 ; Beames and Lipinski, 2020 ; Lovely, 2020 ; Raterman et al, 2020 ; Fernandes and Lovely, 2021 ). We review G E studies applying genome-wide and candidate gene-based approaches using zebrafish and mouse models, especially focusing on gene-ethanol interaction, and their impact on developmental defects ( Table 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Cranial neural crest cells regulate craniofacial development through multiple pathways, including SHH, and Wnt/PCP signaling pathways ( Bush and Jiang, 2012 ; Suzuki et al, 2016 ). Candidate gene-based approaches that target genes involved in these pathways have successfully identified that G E is associated with craniofacial anomalies such as holoprosencephaly and cleft palate ( Eberhart and Parnell, 2016 ; Hong and Krauss, 2018 ; Beames and Lipinski, 2020 ; Lovely, 2020 ; Raterman et al, 2020 ; Fernandes and Lovely, 2021 ).…”
Section: Introductionmentioning
confidence: 99%